01.05 Regulation of arthritis by type 2 innate lymphoid cells. (1st March 2017) - Omata, Yasunori; Lucas, Sébastien; García, Mireia; Wirtz, Stefan; Bozec, Aline; Schett, Georg; Zaiss, Mario M
Abstract : Background: Besides the many well-characterised cellular and molecular components of the innate and adaptive immune system that influence inflammatory processes, recent characterisation of innate lymphoid cells (ILC) has revealed an essential role for these populations in the initiation, regulation and resolution of inflammation. Although low in numbers, ILCs rapidly respond to cytokine and microbial signals and are potent innate cellular sources of multiple pro-inflammatory and immunoregulatory cytokines. ILC2 depends on the transcription factors GATA3 and RORa and produce the type 2 cytokines IL-4, IL-5 and IL-13 upon activation by IL-33 and IL-25. In this project we investigate specifically the role of ILC2s during inflammatory arthritis to unravel their potential therapeutic use. Materials and methods: Tissue samples (spleen, blood and mesenchymal lymph nodes) from K/BxN serum transfer arthritis model (SIA), and collagen induced arthritis (CIA) model were analysed by FACS at different time points (n=5). Human peripheral blood samples were collected from patients with rheumatoid arthritis (RA, n=59) and healthy controls (n=21) and analysed by FACS. Gain (IL-25 and IL-33 minicircle based technology) and loss (RORalpha cre /GATA3 flfl mice) of ILC2 number experiments during the induced arthritis were performed to unravel the role of ILC2s. Results: During both, the SIA and the CIA arthritis mouse models we detected increased frequencies of ILC2s during at early time points after induction of the respective models. In line with these results we detected significantly increased ILC2s in RA patients compared to healthy controls. We could highlight the beneficial effects of ILC2s on arthritis severity because experimentally increasing ILC2 numbers attenuated inflammation, whereas genetically reducing ILC2s exacerbated clinical arthritis severities. Histomorpholocial analysis revealed less bone destruction and decreased osteoclast numbers when ILC2s were increased. Of note, we could detect ILC2 alongside to osteoclasts in the inflamed joints. Conclusions: Our data suggests that ILC2 has a protective effect on arthritic joint destructions.